2019
DOI: 10.7771/1541-5015.1776
|View full text |Cite
|
Sign up to set email alerts
|

Developing Clinical Reasoning Skills Through Argumentation With the Concept Map Method in Medical Problem-Based Learning

Abstract: This study aims to explore the effects of argumentation with the concept map method during medical problem-based learning (PBL) on individual clinical reasoning. Individual clinical reasoning ability was assessed through problem-solving performance and arguments that students constructed during individual clinical reasoning processes. Toulmin's model of argument was utilized as a structure for arguments. The study also explored whether there would be any differences between the firstand second-year medical stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…To optimize the application of mind maps or concept maps, these learning strategies are often combined with several learning models, such as lesson study-based contextual learning models with mind maps (Fadillah et al, 2017), project-based learning models with mind maps (Susilawati, Hernani, & Sinaga, 2017), guided inquiry learning model with mind maps (Prastiwi, Haryani, & Lisdiana, 2018), computerassisted concept map learning model (Liu, Chen, & Chang, 2010), technology-based concept map learning model (Hwang, Wu, & Kuo, 2013), an integrated concept map learning model (Hwang, Kuo, Chen, & Ho, 2014), and a problem-based learning model with concept maps (Si, Kong, & Lee, 2018).…”
Section: Which Is More Effective a Mind Map Or A Concept Map Learning Strategy?mentioning
confidence: 99%
“…To optimize the application of mind maps or concept maps, these learning strategies are often combined with several learning models, such as lesson study-based contextual learning models with mind maps (Fadillah et al, 2017), project-based learning models with mind maps (Susilawati, Hernani, & Sinaga, 2017), guided inquiry learning model with mind maps (Prastiwi, Haryani, & Lisdiana, 2018), computerassisted concept map learning model (Liu, Chen, & Chang, 2010), technology-based concept map learning model (Hwang, Wu, & Kuo, 2013), an integrated concept map learning model (Hwang, Kuo, Chen, & Ho, 2014), and a problem-based learning model with concept maps (Si, Kong, & Lee, 2018).…”
Section: Which Is More Effective a Mind Map Or A Concept Map Learning Strategy?mentioning
confidence: 99%
“…A study by Reiska et al (2018) also found positive changes in the development of students' interdisciplinary knowledge in science when they analysed students' concept maps and assessed the interdisciplinary learning with the concept mapping interdisciplinary quality index (IQI). Another recent study showed that argumentation scaffold through concept mapping during problem-based learning significantly improved and had a transfer effect on the reasoning skills of medical students (Si et al 2019). In a similar vein, the findings of a scientific report on students' perceptions of collaborative concept mapping (CCM) found that the CCM facilitated interdisciplinary learning: students were better able to generate interdisciplinary themes, integrate knowledge, construct new understandings and develop solutions for the problem-based assignment (Everett 2019).…”
Section: Introductionmentioning
confidence: 89%
“…7 Although definitions vary, simulation-based learning suggests that the following elements are required for this instructional strategy: ill-structured problem to solve, student-centered learning, peer collaboration, and instructors as facilitators. 8 Learners approach these cases posed in simulation-based learning in terms of problem representation and solution generation. In the former, the learner must be able to understand the case presented and connect the elements of the experience within an “identifiable structure, bounded in space and time, and containing explicit or implicit messages about the topic being addressed.” 9 For solution generation, students must then work with peers to identify relevant features of the problem space as they engage in shared meaning-making of the problem.…”
Section: Review Of the Literaturementioning
confidence: 99%